Effect of discharge current and electrode size on material removal rate and wear ratio in electrical discharge machining - Khan, Ahsan Ali; Ali, Mohammad Yeakub; Haque, Md. Mohafizul (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malysia, 2010)
In the present study the effect of electrode size and discharge current on material removal rate (MRR) and wear ratio (WR) during electrical discharge machining has been investigated. The work and electrode materials were mild steel and copper respectively. The diameters of the cylindrical electrodes were 9, 15, 20 and 30 mm. Experiments were conducted for three current values of 2.5, 3.5, and 6.5 A. MRR and WR were analyzed with respect to current density. Both MRR and WR were found to increase with the increase of current density. The trend lines are also expressed by two degree parabolic plots and equations. The models were found to be significant with the R-squared and p-values of 0.95 and 0.0001 respectively. Higher current density produces sparks of higher thermal energy which increases MRR and WR. For a constant current, an electrode of smaller diameter exhibited a higher MRR as well as WR.